Dietary Hermetia illucens Larvae Replacement Alleviates Diarrhea and Improves Intestinal Barrier Function in Weaned Piglets Challenged With Enterotoxigenic Escherichia coli K88 - Jin, Xinxin; Yuan, Boyu; Liu, Mingming; Zhu, Mingqiang; Zhang, Xue; Xie, Gaijie; Wu, Wenxiang; Wang, Zifan; Xu, Haidong; Lv, Yantao; Huang, Yanhua; Wang, Wei (Frontiers in Veterinary Science, 2021)
A high-quality protein substitute, Hermetia illucens (black soldier fly) larvae powder is rich in protein, and it is often used in animal feed. This study aimed to investigate the feasibility of replacing fish meal with Hermetia illucens larvae in weaned piglets and the effects on piglets growth performance, intestinal microflora and immune performance. Forty-eight young female weaned piglets (Duroc  Landrace  Large White) were randomly classified into three groups. Each group consisted of eight pens (replicates), with two piglets per pen. Three groups containing different proportions of Hermetia illucens larvae (0, 4%, and 8%) were referred to as C, HI4, and HI8. We first designed a 28-day feeding experiment to detect growth performance; thereafter, the piglets were induced with oral gavage of ETEC K88 and recording diarrhea on day 29 of the experiment. Samples were taken at the 32th day to detect the effect of Hermetia illucens larvae on the immune performance of the weaned piglets. The growth performance of weaned piglets remained unaffected on supplementing feed with Hermetia illucens. The experimental results affirmed that Hermetia illucens larvae could increase the content of Lactobacillus, reduce the content of Streptococcus, and improve intestinal health. Compared with C+K88 group, the diarrhea rate was attenuated for the Hermetia illucens supplemented group. Severe damage was evident in the ileum villi of the C+K88 group, whereas improved integrity was demonstrated by the ileum villi of the HI4+K88 and HI8+K88 groups. Compared with C+K88 group, Hermetia illucens larvae significantly increased expressions of the IL-10 in the intestinal mucosa (P < 0.05) and the Occludin and Claudin-3 (P < 0.05) and reduced expression of the TNF-α (P < 0.05) were reflected in the HI4+K88 and HI8+K88 groups. The results of immunoblotting also validated that the same ETEC K88 treatment of weaned piglets enhanced the expression of tight junction protein in the intestinal mucosa of the Hermetia illucens addition group. ETEC-induced diarrhea will be reduced by the diet of weaned piglets containing Hermetia illucens larvae, ameliorating the immune performance of piglets.